Determination analysis of main dimensions of induction motors for railway propulsion system - Kamar, Syamsul; Lestari, Meiyanne; Luthfiyah, Hilda; Adam Qowiy, Okghi; Syamsuddin Hasrito, Eko; Hidayat, Sofwan (Bulletin of Electrical Engineering and Informatics, 2025)
Induction motors are used in industrial production processes. As for its use as a traction motor, it requires special design and manufacture. The type of induction motor that is widely chosen as a traction motor for railways is a squirrel-cage three-phase induction motor. The main consideration for the selection or design of an induction motor as a railway traction motor is the torque requirement to drive the train. Other parameters that are considered in the selection of an induction motor as a traction motor include available spaces for installation. This research is using a three-phase, 2,300 VAC, 480 kW, and 50 Hz induction motor. By using the application program for determining the parameters of the induction motor, it shows that the motor produces a moderate output coefficient (between maximum and minimum) and produces a torque greater than induction motor torque in general. As a result of the analysis, this induction motor is suitable to be used as a motor for the railway, where greater torque is required.